Neuroscience: impaired decision-making in Parkinson's disease - Herz, D; Bogacz, R; Brown, P (Cell Press, 2016)
When making decisions we combine previously acquired knowledge with the available current information to optimize our choices. A new study shows that Parkinson patients are impaired in using their prior knowledge leading to suboptimal decisions when current information is ambiguous.